PENGARUH MINAT DAN KEPUASAN BELAJAR TERHADAP PEMBELAJARAN ONLINE SISWA - Namang, Veronica Luisa; Marsofiyati; Utari , Eka Dewi (Yayasan Amanah Nur Aman, 2025)
This study aims to analyse the effect of interest and learning satisfaction on student online learning at the Faculty of Economics and Business, State University of Jakarta. The background of this study comes from changes in the education system due to the COVID-19 pandemic which requires learning to be done online. This study examines the relationship between the effectiveness of online learning and students' interest and satisfaction levels. The results show that interest and learning satisfaction have a significant effect on students' online learning. Although there are obstacles such as poor internet connection and lack of interaction from lecturers in the implementation of online learning. This research is expected to provide theoretical contributions in the development of learning methods as well as practical recommendations for lecturers and higher education institutions in improving the quality of online learning as well as the level of student interest and satisfaction.